Penetrance of hypertrophic cardiomyopathy and outcome in sarcomeric mutation carriers. (25th November 2020) - Lorenzini, M; Norrish, G; Field, E; Ochoa, J.P; Cicerchia, M; Akhtar, M.M; Syrris, P; Lopes, L.R; Kaski, J.P; Elliott, P.M
Abstract: Background: Predictive genetic screening of the first degree relatives of patients with hypertrophic cardiomyopathy (HCM) caused by sarcomere protein (SP) gene mutations is current standard of care, but there are few data on long-term outcomes in mutation carriers without HCM. Purpose: To establish the role of sex and genotype in HCM penetrance as well as the rate of major adverse clinical events in SP mutation carriers and following the diagnosis of HCM. Methods: Retrospective analysis of consecutive adult and paediatric SP mutation carriers identified during family screening and who did not fulfill diagnostic criteria for HCM at first evaluation. Results: 321 individuals from 170 families [median age first evaluation 15.2 years (IQR 7.3–32.6); 153 (47.7%) males] were evaluated. Causal SP genes were: MYBPC3 (n=133 (41.4%)), MYH7 (n=77 (24.0%)), TNNI3 (n=51 (15.9%)), TNNT2 (n=40 (12.5%)), TPM1 (n=9 (2.8%)), MYL2 (n=6 (1.9%)), and ACTC1 (n=1 (0.3%)); 4 (1.3%) carried multiple mutations. After a median follow up of 7.4 years (IQR 2.5–12.7), 89 (27.7%) patients developed HCM. Disease penetrance at the age of 50 years was 47% (95% CI 38%-56%). One hundred and fifty three (47.7%) individuals underwent cardiac magnetic resonance (CMR) imaging; among those diagnosed with HCM, 22/89 (24.7%) fulfilled criteria on CMR but not echocardiography. In a multivariable model adjusted for genotype, follow up duration and evaluation with CMR, independent predictors of HCM development were male sex (HR 3.11; CI 1.82–5.32) and abnormal ECG (HR 7.87; CI 4.43–13.97). Patients with MYH7 and multiple mutations were more likely to develop HCM than those with MYBPC3 mutations (HR 2.03; CI 1.04–3.96 and HR 10.13; CI 1.40–72.92, respectively). Disease penetrance was lowest in carriers of TNNI3 mutations (HR 0.13; CI 0.03–0.48). There were no major adverse events in individuals without HCM. Following the diagnosis of HCM, the combined rate of all-cause death, appropriate defibrillator shock or resuscitated cardiac arrest was 1.1%/year [median follow up 4.0 years (IQR 2.1–8.9)]. Conclusions: Approximately 50% of SP mutation carriers develop HCM by the age of 50 and become prone to disease complications during long-term follow-up. Sex, MYH7 mutations and the presence of an abnormal ECG are associated with a higher risk of disease development. CMR should be employed systematically in long-term screening. Funding Acknowledgement: Type of funding source: None